. THE IMPLEMENTATION OF COOPERATIVE LEARNING: STUDENT TEAMS-ACHIEVEMENT DIVISIONS TECHNIQUE IN TEACHING READING COMPREHENSION - Al_Munawwarah, Sophia Fithri (2013)
This study aims to investigate the benefits of implementing cooperative learning with STAD technique in teaching reading comprehension and the students' responses toward the implementation of STAD technique. This study was conducted based on the assumption that STAD technique can be a recommended technique in teaching English for EFL students (Wichadee, 2006). The study employed case study approach, and the data were collected through observation, interview, written documents, and dependent t-test to gain relevant data. The results of the study were in line with the previous findings from the studies conducted by Slavin (1995) and Wichadee (2006) that STAD technique is effective to be used as teaching technique since the students show great attention during the lesson. The research findings of this study discover some benefits of STAD technique, as follows: (1) engaging students in reading activity; (2) increasing students' motivation to practice actively in the learning process; (3) helping students to solve their problems in comprehending the texts; (4) developing students' social skill; (5) creating enjoyable learning atmosphere; and (6) enhancing students' reading comprehension skills. In addition, the students' responses toward the implementation of STAD technique in teaching reading were positive. Based on these findings, it is recommended that STAD technique be implemented in teaching reading comprehension. Key terms: Cooperative Learning, reading comprehension, STAD technique, recount text.